The hypoxia-regulated transcription factor DEC1 (Stra13, SHARP-2) and its expression in human tissues and tumours. - Turley, H; Wykoff, C; Troup, S; Watson, P; Gatter, K; Harris, A (2004)
DEC1, also known as SHARP-2 or Stra13, is an important molecule in embryonic differentiation and has recently been identified to be strongly inducible by hypoxia. Its distribution in normal human tissues and most tumour types is unknown. In the present study, a polyclonal antiserum to a 10-amino acid peptide from DEC1 has been raised. Using this antiserum, DEC1 was shown to be widely expressed in most normal human tissues, but usually only in a proportion of cells and typically with a nuclear localization. In tumours, expression was either augmented (the commonest pattern) or occasionally decreased. Similarly, in most normal tissues, low or absent expression was observed in endothelial cells, whereas in many tumour samples endothelium was usually strongly positive. In tumours, there was a striking pattern of staining seen in connection with areas of necrosis, with absence of DEC1 expression within a zone of morphologically viable cells immediately adjacent to the necrotic zone. This suggests that while DEC1 may be up-regulated by hypoxia in cancer, in more extreme hypoxia it may have a role in cell death. Its interrelationship with other hypoxically regulated molecules, such as the hypoxia-inducible factors or carbonic anhydrase IX, and differentiation of tumours now requires further investigation.